Medieval [videorecording (DVD)] - Jákl, Petr, 1973-; Foster, Ben, 1980-; Lowe, Sophie; Schweiger, Til, 1963-; Goode, Matthew, 1978- (Paramount Home Entertainment, 2022)
Jan Žižka was a daring mercenary leader and one of the greatest warriors in history. After the death of its emperor, the Holy Roman Empire plummets into chaos while corrupt kings battle for control of the empty throne, so Jan leads a rebel army to ensure tyranny does not ensue.